2019
DOI: 10.3390/ijerph16203821
|View full text |Cite
|
Sign up to set email alerts
|

How Do Nurses Cope with Shift Work? A Qualitative Analysis of Open-Ended Responses from a Survey of Nurses

Abstract: Nurses are frequently required to engage in shift work given the 24/7 nature of modern healthcare provision. Despite the health and wellbeing costs associated with shift work, little is known about the types of coping strategies employed by nurses. It may be important for nurses to adopt strategies to cope with shift work in order to prevent burnout, maintain wellbeing, and ensure high quality care to patients. This paper explores common strategies employed by nurses to cope with shift work. A workforce survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 66 publications
(126 reference statements)
1
41
0
1
Order By: Relevance
“…Therefore, our findings suggest that a wide range of coping strategies are employed by Polish nurses when dealing with stress. Similar results were observed in a recent study among 449 shift working nurses in Australia, although they showed the effective use of such coping strategies was hindered by sleep disturbances (Savic et al., 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, our findings suggest that a wide range of coping strategies are employed by Polish nurses when dealing with stress. Similar results were observed in a recent study among 449 shift working nurses in Australia, although they showed the effective use of such coping strategies was hindered by sleep disturbances (Savic et al., 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Taken together, all these factors contribute to define the individual worker’s ability to manage the side effects of shift work and determine the efficacy of the adopted coping strategies (Savic et al, 2019 ). First, a timely estimation of the individual workers’ tolerance may help allocate workers to a certain shift pattern.…”
Section: Future Directions In the Management Of Night Shift Nursesmentioning
confidence: 99%
“…Different strategies are available for managing sleep loss in shift work. Sleep medicine has come a long way due to increased public awareness, as highlighted by the study of Savic et al (2019), who reported that the nurses in their study had already adopted health-promoting coping strategies with their night shifts [32], including health practices of physical activity, healthy eating, engaging with social support and leisure, mindfulness, managing time, and work-related coping strategies. Nevertheless, the online platforms of mHealth [33] and cognitive behavioural therapy for insomnia (CBTi) [34] are resourceful, easily accessible materials for shift workers.…”
mentioning
confidence: 99%